Persistence of fecal indicator bacteria and associated genetic markers from wastewater treatment plant effluents in freshwater microcosms. (16th December 2021) - Chern, Eunice C.; Wymer, Larry; Brenner, Kristen; Oshima, Kevin; Haugland, Richard A.
Abstract: Limited information exists on the environmental persistence of genetic markers for fecal indicator bacteria (FIB) in treated wastewaters. Here, the decay rate constants of culturable cells and genetic markers for four diverse groups of FIBs, such as enterococci, Clostridium, Escherichia coli, and Bacteroides, were investigated in freshwater microcosms seeded with disinfected and non-disinfected secondary-treated wastewaters. Decay rate constants of genetic markers and culturable cells varied significantly among the different FIB groups. Water temperatures (winter vs. fall/spring/summer) significantly affected the decay of all genetic marker and cell types; however, genetic marker decay were not found to be significantly different in disinfected (chlorination/ultraviolet) and non-disinfected wastewater-seeded microcosms or, for example, lake- and river-receiving waters. No evidence was seen that decay rate constants of FIB genetic markers from treated wastewater were substantially different from those observed in similar, previously reported microcosm studies using raw sewage. Unexpected relationships between decay rate constants of genetic markers and culturable cells of Bacteroides were observed. Results suggest that decay rate constants of FIB genetic markers determined from other studies may be applicable to treated wastewaters. Results of this study should be informative for ongoing efforts to determine the persistence of FIB genetic markers relative to surviving pathogens after wastewater treatment. HIGHLIGHTS: The influence of wastewater treatment on the persistence of FIB genetic markers was examined. Diverse FIBs in different freshwaters and temperatures were investigated. Disinfection did not significantly affect genetic marker decay. Genetic marker decay rate constants were Bacteroides > E. coli, Enterococcus > Clostridium . Genetic markers may better predict the presence of pathogens than culturable FIB in disinfected wastewater.